Knowledge graphs in psychiatric research: potential applications and future perspectives - Freidel, Sebastian; Schwarz, Emanuel (Acta psychiatrica Scandinavica, 2024)
Background Knowledge graphs (KGs) remain an underutilized tool in the field of psychiatric research. In the broader biomedical field KGs are already a significant tool mainly used as knowledge database or for novel relation detection between biomedical entities. This review aims to outline how KGs would further research in the field of psychiatry in the age of Artificial Intelligence (AI) and Large Language Models (LLMs). Methods We conducted a thorough literature review across a spectrum of scientific fields ranging from computer science and knowledge engineering to bioinformatics. The literature reviewed was taken from PubMed, Semantic Scholar and Google Scholar searches including terms such as “Psychiatric Knowledge Graphs”, “Biomedical Knowledge Graphs”, “Knowledge Graph Machine Learning Applications”, “Knowledge Graph Applications for Biomedical Sciences”. The resulting publications were then assessed and accumulated in this review regarding their possible relevance to future psychiatric applications. Results A multitude of papers and applications of KGs in associated research fields that are yet to be utilized in psychiatric research was found and outlined in this review. We create a thorough recommendation for other computational researchers regarding use-cases of these KG applications in psychiatry. Conclusion This review illustrates use-cases of KG-based research applications in biomedicine and beyond that may aid in elucidating the complex biology of psychiatric illness and open new routes for developing innovative interventions. We conclude that there is a wealth of opportunities for KG utilization in psychiatric research across a variety of application areas including biomarker discovery, patient stratification and personalized medicine approaches.
Gesehen am 18.11.2024